Exploring How Neighborhood Environments Shape Quality of Life in Aging Populations - Yongmei, Hou (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Background: The community is the primary living environment for the elderly, and the neighborhood environment plays a critical role in shaping their health status and quality of life and contributes to the formation of a good social atmosphere, but research on the impact of neighborhood environment on residents' quality of life is mostly in the form of case studies, and there are not many comprehensive analysis papers. Objective: This review aims to synthesize the empirical evidence on the impact of the neighborhood environment on the quality of life of the elderly, with a focus on the physical and mental health benefits of age-friendly community design. Methods: A literature retrieval was used to review empirical papers published in English or Chinese in the past 11 years in Google Scholar, Pubmed, CNKI, and Wanfang databases. Results: Forty-eight articles were included. The neighborhood environment can affect both physical health and quality of life, as well as mental health and social relationships. Conclusion: This review underscores the need for further research on the intersection of neighbourhood environment and healthy ageing, particularly in the development of more robust research tools and the exploration of understudied populations.